2020
DOI: 10.1186/s42269-020-00400-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing time on productivity of Bt and non Bt cotton under climate change

Abstract: Background: Climate change affects cotton production systems in multiple ways, and the impacts are expected to influence the national economy of India. The weather conditions prevailing during squaring, flowering and boll development stages determine the seed cotton yield. The needs for adaptation connected to optimizing the timing of critical growth stages to minimize stresses and enhance resource utilization. The adjusting of sowing times proved to be an important management technique for improving seed cott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Reduction in yield parameters in later sowing dates might be due to poor environmental conditions particularly minimum temperature falling at the time of reproductive stage (Manjeet et al 2019). The gradual reduction in boll weight by late sowing was reported by Sankaranarayanan et al (2020).…”
Section: Yield Attributesmentioning
confidence: 88%
See 1 more Smart Citation
“…Reduction in yield parameters in later sowing dates might be due to poor environmental conditions particularly minimum temperature falling at the time of reproductive stage (Manjeet et al 2019). The gradual reduction in boll weight by late sowing was reported by Sankaranarayanan et al (2020).…”
Section: Yield Attributesmentioning
confidence: 88%
“…The reproductive development in late sown crop was affected by cooler temperature and low light, which reduced photosynthetic activity and transport of carbohydrates to fruit structures (Gormus and Yucel 2002;Liu et al 2015;Zhang et al 2014). The lesser yield was due to sub-optimal weather conditions in late sowing date as reported by Gormus and Yucel (2002) and Sankaranarayanan et al (2020) Amongst years of experimentation, 2018-19 resulted as higher performance of G. arboreum, despite the fact that the genotypes were repeated following similar management practices in all three years. The analysis of weather parameters found that seasonal rainfall received were 472.3, 396.8 and 686.6 mm during 2017-18, 2018-19 and 2019-20, respectively.…”
Section: Seed Cotton Yieldmentioning
confidence: 98%
“…Plant competition for resources in higher population resulted in smaller cotton plant with a higher resource use efficiency (Liu et al, 2020) but results in poor boll load and delayed late-season leaf senescence (Luo et al, 2018). Increased plant density would be beneficial to cotton yield in the lower fertility field (Dong et al, 2010;Sankaranarayanan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Plant competition for resources in higher population resulted in smaller cotton plant with a higher resource use efficiency (Liu et al, 2020) but results in poor boll load and delayed late-season leaf senescence (Luo et al, 2018). Increased plant density would be beneficial to cotton yield in the lower fertility field (Dong et al, 2010;Sankaranarayanan et al, 2018). Inappropriate planting density, either low or high may exhibit enormous risk for yield formation (Khan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%